Quantifying the user experience : practical statistics for user research - Sauro, Jeff.; Lewis, James R., 1953- (Amsterdam ; Waltham, MA : Elsevier/Morgan Kaufmann, 2012)
"The primary purpose of this book is to provide a statistical resource for those who measure the behavior and attitudes of people as they interact with interfaces. The focus is on methods applicable to practical user research, based on our experience, investigations, and reviews of the latest statistical literature"--
Machine generated contents note: 1. Introduction and How to Use This Book -- 2. Quantifying User Research -- 3. How Precise Are Our Estimates? Confidence Intervals -- 4. Did We Meet or Exceed Our Goal? -- 5. Is There a Statistical Difference between Designs -- 6. What Sample Sizes Do We Need? Part. 1: Summative Studies -- 7. What Sample Sizes Do We Need? Part. 2:Formative Studies -- 8. Standardized Usability Questionnaires -- 9. Six Enduring Controversies in Measurement and Statistics -- 10. Wrapping Up.
Includes bibliographical references and index.
Keywords: User interfaces (Computer systems) -- Testing -- Statistical methods